2017
DOI: 10.3389/fnhum.2017.00305
|View full text |Cite
|
Sign up to set email alerts
|

Dancing or Fitness Sport? The Effects of Two Training Programs on Hippocampal Plasticity and Balance Abilities in Healthy Seniors

Abstract: Age-related degenerations in brain structure are associated with balance disturbances and cognitive impairment. However, neuroplasticity is known to be preserved throughout lifespan and physical training studies with seniors could reveal volume increases in the hippocampus (HC), a region crucial for memory consolidation, learning and navigation in space, which were related to improvements in aerobic fitness. Moreover, a positive correlation between left HC volume and balance performance was observed. Dancing s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
117
1
11

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(131 citation statements)
references
References 48 publications
2
117
1
11
Order By: Relevance
“…A study in healthy elderly people (n=26, mean age= 67.9 years, SD=3.3 years) demonstrated increases in hippocampal volume after intensive training (twice a week for 6 months, followed by once a week for 12 months; 90 minutes training). 65 The hippocampal changes were seen in people participating in fitness sport and dance; however, the changes were more pronounced and widespread in the dance intervention, including the right subiculum and left DG. Future studies should investigate whether such 'combination studies' might exert larger effects on the hippocampal network than single modality studies.…”
Section: Plasticity Of the Hippocampal Networkmentioning
confidence: 96%
“…A study in healthy elderly people (n=26, mean age= 67.9 years, SD=3.3 years) demonstrated increases in hippocampal volume after intensive training (twice a week for 6 months, followed by once a week for 12 months; 90 minutes training). 65 The hippocampal changes were seen in people participating in fitness sport and dance; however, the changes were more pronounced and widespread in the dance intervention, including the right subiculum and left DG. Future studies should investigate whether such 'combination studies' might exert larger effects on the hippocampal network than single modality studies.…”
Section: Plasticity Of the Hippocampal Networkmentioning
confidence: 96%
“…However, it should be noted that those studies on balance have found an increase not only in the right but also in both the left and the right hippocampus [103][104][105][106]. Looking at the results of the Yoga and mind-body studies, a similar inhomogeneous picture of the affected hemisphere is shown [34,40,41].…”
Section: -Week Hatha Yoga Increases Right Hippocampal Density Compamentioning
confidence: 79%
“…Furthermore, the balance exercises, which are an integral part of the Yoga exercises, could contribute to the effect in the hippocampus taking into account the significant role of the right hippocampus in spatial orientation [101] and the consolidation of motor sequences [102]. Several studies have shown structural increase of the hippocampus after interventions on balance [103][104][105][106].…”
Section: -Week Hatha Yoga Increases Right Hippocampal Density Compamentioning
confidence: 99%
“…Physical activity programs for older adults can bring greater benefits when cognitive tasks are integrated. For example, challenging dance programs that combine aerobic fitness, sensorimotor skills and cognitive demands are promising in counteracting the decline in physical and cognitive abilities during aging (Müller et. al., 2017;Rehfeld et.…”
Section: Physical Activity Programs Including Cognitive Tasksmentioning
confidence: 99%